High-power pulse repetitive HF(DF) laser with a solid-state pump generator. (November 2015) - Velikanov, S.D.; Domazhirov, A.P.; Zaretskiy, N.A.; Kazantsev, S.Yu.; Kononov, I.G.; Kromin, A.A.; Podlesnykh, S.V.; Sivachev, A.A.; Firsov, K.N.; Kharitonov, S.V.; Tsykin, V.S.; Shchurov, V.V.; et al.
Abstract: Operation of a repetitively pulsed electric-discharge HF(DF) laser with an all-solid-state pump generator based on FID switches is demonstrated. The energy stored in the pump generator capacitors was at an open-circuit voltage of and a discharge pulse repetition rate of . The specific energy extractions were 3.8 and for the HF and DF lasers, respectively. The possibilities of improving the output laser characteristics are discussed.